Introduction To Special Issue Popular Culture In Asia - Bratzel, John (Penerbit Universiti Sains Malaysia (USM Press), 2011)
Popular culture is not new, but the formal academic study of popular culture is. It began about 50 years ago and the discipline has grown considerably during that time. Because East Asia has many diverse elements and cultures, all of which deserve serious examination, it is completely appropriate that there should be an academic organisation dedicated to its study. The first East Asian Popular Culture Association Conference∗ was held in Taipei from 1 to 4 September 2011. At that meeting, scholars from 18 nations delivered almost 100 papers including three presentations by prominent scholars who delivered keynote talks. The sessions were lively and thoughtful and included serious discussion of the issues that participants developed. But not all the time was devoted to formal sessions. Attendees enjoyed a walking tour of the ShiDa night market as well as an all-day tour of the greater Taipei area to gain a better sense of the complex and beautiful culture of Taiwan. Good food and lively talk heightened the enjoyment of the conference.